2014
DOI: 10.2106/jbjs.m.00018
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Postoperative Complications and Mortality Following Total Knee Arthroplasty

Abstract: Patient age and diabetes increased the risk of mortality after primary total unilateral knee arthroplasty. Predictive factors impacting the development of postoperative complications included an ASA classification of ≥3, increased operative time, increased age, and greater body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
237
7
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(280 citation statements)
references
References 42 publications
16
237
7
20
Order By: Relevance
“…Moreover, chronic obstructive pulmonary disease recently was shown to be associated with carotid artery wall thickening, placing patients at greater danger for ischemic events [21]. Furthermore, advanced operative time has been linked to numerous postoperative adverse events after orthopaedic surgery, potentially owing to the effect of anesthesia time or to a more complicated procedure [3,36]. An important difference in the results of our study with those of Mortazavi et al [29] is that general anesthesia was not independently associated with CVA.…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, chronic obstructive pulmonary disease recently was shown to be associated with carotid artery wall thickening, placing patients at greater danger for ischemic events [21]. Furthermore, advanced operative time has been linked to numerous postoperative adverse events after orthopaedic surgery, potentially owing to the effect of anesthesia time or to a more complicated procedure [3,36]. An important difference in the results of our study with those of Mortazavi et al [29] is that general anesthesia was not independently associated with CVA.…”
Section: Discussioncontrasting
confidence: 63%
“…Postoperative variables including length of stay as well as 30-day complication rates and mortality were calculated ( Table 2). Complications were categorized based upon the previous reports [4]. Major systemic complications included pulmonary embolism (PE), acute renal failure, cardiac arrest or myocardial infarction, sepsis or septic shock, stroke, unplanned intubation, coma over 72 h, or death.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most common and important diseases thought to be associated with an increased risk of perioperative complications among patients undergoing TKA. Previous studies have reported higher rates of infection [8,18,20,21,28], wound complications [5,6], greater risk of deep vein thrombosis [27,29], poorer outcomes [4,13,14,22,25], and higher mortality [2] in patients with DM undergoing TKA compared with patients without DM. Unfortunately, the prevalence of DM among patients undergoing TKA has been steadily increasing [11,15] and orthopaedic surgeons will be faced with a growing number of surgical patients with DM.…”
Section: Introductionmentioning
confidence: 99%